Perencanaan Tempat Evakuasi Bencana Banjir Berbasis Teknologi Sistem Imformasi Geografis (SIG) ( Studi Kasus Kota Pekanbaru Kecamatan Rumbai) - Fernando, Rangga; Sujatmoko, Bambang; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Floods that occurred in City of Pekanbaru hit the region along the river siak one of which subdistrict Rumbai. Impacts of of the flooding detrimental to society from materials or people’s life. One of the solution to minimize impact is to make plan evacuation route and flood shelter mapping of with Geographic Information Systems (GIS). The determination of the place of evacuation based on the location of the flood shelter must be located outside of the area of flooding by doing a field survey. The place of evacuation have two criteria, namely in the form of permanent buildings such as public facilities, and building a non permanent tent of the evacuation. Some locations that can be used as evacuation place, namely Al-Jihad Mosque, Al-ikhlas Mosque, MDA Aula Rumbail, Mosque Nurul Haq, M Nurul Mosque, Empty Land and parking areas of the stadium. Plan evacuation route of mapping based analysis of the data by method of algorithm djikstra for result pathways of efficient and effective evacuation. Algorithm djikstra analysis resulting one evacuation routes in the Palas Village and six evacuation routes in the Sri Meranti Village. Evacuation routes in the Palas Village can go to the evacuation place of Al-Jihad Mosque, being in the Sri Meranti Village can go to the evacuation place Al-Ikhlas Mosque, MDA Aula Rumbai, Nurul Haq Mosque, M Nurul Mosque, vacant land and Stadium Parking Area.Keywords : Evacuation route, Algorithm djikstra, SIG, Floodshelter.